An alternative method to recover Toxoplasma gondii from greenery and fruits. Issue 5 (1st November 2016) - de Souza, Carla Zangari; Rafael, Katyelle; Sanders, Ana Paula; Tiyo, Bruna Tiaki; Marchioro, Ariella Andrade; Colli, Cristiane Maria; Gomes, Mônica Lúcia; Falavigna-Guilherme, Ana Lúcia
Abstract: Toxoplasma gondii oocysts are an important form of contamination with a high dispersion in the environment, but their detection is still a challenge. This study evaluated the recovery of oocysts from strawberries and crisphead lettuce. Samples (250 g of strawberries or one head of lettuce) were experimentally inoculated with 10, 10 2, 10 3 and 10 4 T. gondii oocysts, by two separate processes, spot dripping and immersion. Then, 50 g of each sample was washed, filtered through a cellulose ester membrane, and concentrated by centrifugation. Three aliquots were taken for DNA extraction in a direct way, after freeze–thaw (FT) cycles or ultrasound (US), followed by PCR (B22-B23 and Tox4-Tox5 primers). The T. gondii DNA was amplified with the primers B22-B23 in all samples contaminated by dripping and when DNA extraction was carried out after FT or US. These techniques may be useful in epidemiological surveillance in the control of this zoonosis.